Design of a Casting Die in CATIA - Rokyta, Lubos; Bilek, Ondrej (Manufacturing Technology Journal, 2012)
Design of a Casting Die made of aluminium alloy components using CATIA software is described in the article. Computer aided design and construction is necessary for the creation of each part. A lot of tools are implemented in the CATIA program. These tools are used to design cast parts easily. A few aspects are necessary for this technology. To achieve a quality fine-grained structure without porosity and the oxide inclusions, a possibility to observe the casting, solidification, tempering, easy creation of core and cavity, possibility of rapid design whole mould. This factors influence efficiency of construction, quality of the product and production economy. Use of CAx technologies is necessary to meet the requirements [7]. Simulation in some simulating program occurred before this construction. These programs work on basis of Navier-Stokes law and law of conservation of momentum [4]. Combination of these products influences efficiency, productivity and financial expenses.
Keywords: Casting Die; Construction; CAD; CATIA; Computer Aided Design; Pressure Casting